When x-rays alter the course of your experiments*This manuscript has been authored by UT-Battelle, LLC, under contract DE-AC05-00OR22725 with the US Department of Energy (DOE). The US government retains and the publisher, by accepting the article for publication, acknowledges that the US government retains a nonexclusive, paid-up, irrevocable, worldwide license to publish or reproduce the published form of this manuscript, or allow others to do so, for US government purposes. DOE will provide public access to these results of federally sponsored research in accordance with the DOE Public Access Plan. (9th August 2021) - Bras, Wim; Myles, Dean A A; Felici, Roberto
Abstract: The continuing increase in the brilliance of synchrotron radiation beamlines allows for many new and exciting experiments that were impossible before the present generation of synchrotron radiation sources came on line. However, the exposure to such intense beams also tests the limits of what samples can endure. Whilst the effects of radiation induced damage in a static experiment often can easily be recognized by changes in the diffraction or spectroscopy curves, the influence of radiation on chemical or physical processes, where one expects curves to change, is less often recognized and can be misinterpreted as a 'real' result instead of as a 'radiation influenced result'. This is especially a concern in time-resolved materials science experiments using techniques as powder diffraction, small angle scattering and x-ray absorption spectroscopy. Here, the effects of radiation (5–50 keV) on some time-resolved processes in different types of materials and in different physical states are discussed. We show that such effects are not limited to soft matter and biology but rather can be found across the whole spectrum of materials research, over a large range of radiation doses and is not limited to very high brilliance beamlines.